Is Sole Lumbar Bone Mineral Density Measurement Sufficient in Postmenopausal Patients with Vertebral Fractures? - Fulya Demircioğlu Güneri; Fatih Karaarslan; Mustafa Turan; Ersin Odabaşı (Ahi Evran Medical Journal, 2024)
Purpose: This study aimed to assess the adequacy of using Dual X-ray Absorptiometry (DXA) for evaluating lumbar bone mineral density (BMD) and T-scores in patients with vertebral fragility fractures, without considering thoracic and lumbar X-ray images.